2012
DOI: 10.1017/s0144686x12000165
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor adventure and successful ageing

Abstract: This article explores how outdoor adventure activities in a New Zealand communitybased programme are experienced and understood as successful ageing strategies. Outdoor adventures are seen as positive leisure experiences that include challenging physical activity, social engagement and the natural environment. Using a sequential exploratory mixed-methods design, a combination of seven interviews and a survey (N = ) were conducted with a Third Age adventures group. The research outcomes confirmed the attracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 43 publications
1
40
0
2
Order By: Relevance
“…This study confirms the importance of ensuring that PA is enjoyable, as very few people stated that they were active for the health benefits alone . The outdoor environment has been shown to encourage people to be more active in their local areas, but this is mitigated by the influence of poor weather and dark nights on engagement in PA and attendance at activity sessions . This study has found that engagement in PA is seasonal, with activity levels increasing in the warmer months.…”
Section: Discussionsupporting
confidence: 71%
“…This study confirms the importance of ensuring that PA is enjoyable, as very few people stated that they were active for the health benefits alone . The outdoor environment has been shown to encourage people to be more active in their local areas, but this is mitigated by the influence of poor weather and dark nights on engagement in PA and attendance at activity sessions . This study has found that engagement in PA is seasonal, with activity levels increasing in the warmer months.…”
Section: Discussionsupporting
confidence: 71%
“…Older individuals are less likely to want to escape such pressures as they tend to be retired, to have an established network of friends, and to be less involved in raising a family (Sugerman, 2001). Most research has concentrated on older or 'third age' participants aged over 55 years, yet this is limited (Boyes, 2013). Older adventure tourists are motivated by the potential for excitement and thrills during participation in 'safe' soft adventure activities, feeling youthful again and enjoying bodily rejuvenation (Cater, 2000;Patterson & Pan, 2007).…”
Section: Influences On the Motivations Of Outdoor Adventure Activity mentioning
confidence: 99%
“…Older adults involved in outdoor adventure programmes designed specifically for over 55 year-olds predominantly are motivated by the natural environment, developing their skills in particular adventure activities, physical activity, meeting like-minded people and developing new friendships (Sugerman, 2001). Benefits for older outdoor recreational adventurers include general physical improvements, a positive impact on well-being, camaraderie, social engagement and support, occupying one's mind, and gaining a positive image as older adults (Boyes, 2013). …”
Section: Influences On the Motivations Of Outdoor Adventure Activity mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, “Active Ageing Australia” promotes physical activity for a lifetime of health and well-being, considering that physical activity enriches persons’ lives by supporting their ability to maintain independent, healthy lifestyles and participate in and contribute to the community 19. Other intervention programs encourage physical activity by offering a personal choice-based and telephone-assisted training program,20 enhancing pro-social behavior and volunteerism,21 or outdoor activities (such as biking),22 as strategies for promoting active aging.…”
Section: Introductionmentioning
confidence: 99%